Comparison of gut microbiota profile in celiac disease, non-celiac gluten sensitivity and irritable bowel syndrome: A systematic review - Transeth, Elin Lund; Dale, Hanna Fjeldheim; Lied, Gülen Arslan (Turkish Journal of Gastroenterology, 2020)
Gut microbiota is vital for human health. Shifts in the microbial diversity can affect bacterial function, and dysbiosis is associated with a variety of gastrointestinal disorders, including celiac disease (CD) and irritable bowel syndrome (IBS). The distinction between IBS and non-celiac gluten sensitivity (NCGS) is unclear, and it is conceivable that the gut microbiota profile of these patients may overlap. To our knowledge, no existing literature has evaluated the microbial characteristics in CD, IBS, and NCGS. Hence, this systematic review aims to compare the gut microbiota profile in these three diagnoses. A literature search was conducted in PubMed (Medline) until April 2019. Studies investigating bacterial diversity in the gut of patients with CD, IBS, and NCGS were eligible. Inclusion criteria were observational studies and randomized controlled trials reporting bacterial profile at baseline. Ninety-one articles were identified, of which 13 trials were eligible for inclusion. Overall, the bacterial composition of the gut microbiota of patients with CD and those with IBS shared the many similarities. The microbial richness was correspondingly reduced in these patient-groups compared with healthy controls, but this was not reported for NCGS. Our findings suggest that the bacterial profiles of patients with IBS and CD share certain disease-specific trends. Fewer similarities were observed between the bacterial profiles of patients with IBS and NCGS. Notably, the data are limited; thus, no solid conclusions can be made on the basis of these findings alone. The suggested trends can be a valuable basis for further research.